2017
DOI: 10.1051/matecconf/201713104014
|View full text |Cite
|
Sign up to set email alerts
|

Remaining Useful Life Prediction of Gas Turbine Engine using Autoregressive Model

Abstract: Abstract. Gas turbine (GT) engines are known for their high availability and reliability and are extensively used for power generation, marine and aero-applications. Maintenance of such complex machines should be done proactively to reduce cost and sustain high availability of the GT. The aim of this paper is to explore the use of autoregressive (AR) models to predict remaining useful life (RUL) of a GT engine. The Turbofan Engine data from NASA benchmark data repository is used as case study. The parametric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Mathew et al [7] found that the random forest algorithm outperformed others in estimating the remaining useful life (RUL). Ahsan et al [8] proposed a semi-supervised model to investigate the impact of limited labeled training data on estimating remaining useful life (RUL). Several studies have recognized the superior performance of the convolutional neural network (CNN) approach compared to the long short-term memory (LSTM) method [12][13][14].…”
Section: Related Workmentioning
confidence: 99%
“…Mathew et al [7] found that the random forest algorithm outperformed others in estimating the remaining useful life (RUL). Ahsan et al [8] proposed a semi-supervised model to investigate the impact of limited labeled training data on estimating remaining useful life (RUL). Several studies have recognized the superior performance of the convolutional neural network (CNN) approach compared to the long short-term memory (LSTM) method [12][13][14].…”
Section: Related Workmentioning
confidence: 99%
“…Monitoring these results makes it possible to track the performance degradation of gas turbines. The data can be used for prediction and decision-making on maintenance and repair of gas turbine units [16,17].…”
Section: Operation Of the Techniquementioning
confidence: 99%
“…In comparison to alternative frameworks that can fulfill similar requirements, LCC involves analyzing cash flow by calculating the difference between cash inflow and cash outflow associated with system acquisition and ownership. The study is conducted at the Gas District Cooling (GDC) plant, equipped with gas-turbine ships responsible for power production (Ahsan and Lemma, 2017;Akbar and Mokhtar, 2017), along with Electrical Chillers and TES tanks. Static parameters, selected either during installation or the feasibility study, serve as the foundation for predicting the monetary or cost aspects in current life cycle costing models.…”
Section: Introductionmentioning
confidence: 99%